TOM Phillips's illustrations for the Folio edition of waiting for Godot - Parra, Claudia [UNESP]; Harris, Peter James [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2018)
In the light of the imagery associated with Samuel Beckett's Waiting for Godot, in set designs, posters and book covers, the present article examines Tom Phillips's illustrations for the Folio Society edition of Waiting for Godot (2000). Considering that Phillips's images embody a particular style in form and structure, functioning as pictorial elements recalling contexts, images and relations, we propose that the artist expands the visual interpretative frame of the play, predicating his work on the premise that readers will have had previous contact with the work either in performance or as a text.
Keywords: Art; Illustrated Book; Samuel Beckett; Tom Phillips